Assessment of physical education model in summer health-improving camp, aimed at cultivating interest to physical exercises in teenagers - Yezersky V. I. (Kharkov National Pedagogical University, 2010)
Article presents characteristic of teenagers' physical education model in summer health-improving camp, which provides social-pedagogical conditions for cultivating interest in physical exercises. This model is based on realization of principles of systematic, activity and person-oriented approaches to development of physical culture of a person. Assessment of teenagers' attitude to educational health-improving physical activities in summer health-improving camp is presented basing on results of conducted survey.